Representações de leitura do livro didático de português do ensino fundamental maior - TRINDADE, Rosinélio Rodrigues da (Universidade Federal do Pará, 2014)
In this research, we take the Portuguese textbook as an object of research and guide our work by the question:: What makes a book be a textbook? Such question, which at first may seem obvious, due to the opacity of the unique aspects that take part in said materials’ constitution, revealed that the textbook is a multifaceted and complex objetct situated in a new field of academic research. Among many possibilities of inserting the textbook in the context of human concerns, there are two that are introduced in that research as possibilities to think about it as object of its own field of research: (i) the one which begins from the comprehension of the textbook as an object that bears materiality and visuality, where elements such as typography, diagramation, use of colors, choice of images, among many others, participate in the reading process as much as the linguistically constituted verbal text , and (ii) the one which considers the book as object that bearsa textual-discursive materiality by means of witch it responds to many places and interests which are often contradictory, as far as it tries to satisfy different expectations laid upon it. In this sense, we consider that the production of textbooks firstly aims at a didactic project – due to which are created representations of reading – but also makes it an important product of a promising market and very profitable as well. This leads us to believe that the textbook functions mainly as an object of consumption/distribution instead a support to the teaching and learning of Portuguese. The research follows on the theories of Discourse Analysis of French tradition, considering the ideas of authors such as Pêcheux, Maingueneau, Possenti, Authier-Revuz; of the history of reading based on Chartier, Fairchild, Choppin, Freitag et al, Oliveira et al among others. The research corpus comprises a collection of Portuguese textbooks (for the final grades of elementary school) collected from the last PNLD (“Plano Nacional do Livro Didático”, Textbook National Plan)/2011 which was chosen by most of the urban schools in the municipality of Cametá/Pará; field notes with the report of research experiences; and a questionnaire of open questions on the process of choice of the textbook of Portuguese in those schools.